Best of International Stereotactic Radiosurgery Society Congress 2013: stereotactic body radiation therapy. Part II: nonspinal tumors. (September 2013) - Lo, Simon S; Chang, Eric L; Ryu, Samuel; Chung, Hans; Slotman, Ben J; Teh, Bin S; Sahgal, Arjun
The 11th biennial International Stereotactic Radiosurgery Society Congress represented another historical gathering of professionals in the field of stereotactic radiosurgery. This congress was held on 16–20 June 2013 in Toronto (ON, Canada), and the chairman was Arjun Sahgal, co-chair was Michael Schwartz and president of the society was Jean Regis. The congress attracted 550 attendants from all over the world and over 300 abstracts were presented. Among the abstracts presented, 62 (36 oral) were pertaining to stereotactic body radiation therapy (SBRT). Exciting new findings were presented by colleagues from North America, Europe and Asia. This short conference scene (part II) provides a summary of the best abstracts on SBRT for nonspinal tumors presented in the congress. A separate conference scene on SBRT for spinal tumors (part I) also appears in this issue of Future Oncology .